2017
DOI: 10.4103/jcas.jcas_118_17
|View full text |Cite
|
Sign up to set email alerts
|

Management of stretch marks (with a focus on striae rubrae)

Abstract: Stretch marks are one of the most common benign cutaneous lesions and encountered esthetic problems. Striae rubrae and striae albae can be differentiated on the basis of clinical appearance. Histologically, disturbances of the dermal fiber network and local expression of receptors for sexual steroids have been detected. The epidermal changes are secondary. Prevention of stretch marks using topical ointments and oils is debatable. Treatment of striae rubrae by lasers and light devices improves appearance. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 55 publications
0
32
0
5
Order By: Relevance
“…Estudos histológicos mostram que as fibras de elastina se exibem rompidas, entrelaçadas, desorganizadas, delgadas e em forma de fio emergindo a derme adventícia, além disso é possível observar que as mudanças ocorrem em toda a estrutura conjuntiva dérmica, com diminuição no número e volume dos elementos da pele. As áreas mais acometidas são os seios, abdômen, glúteos e coxas, principalmente em mulheres [3][4][5].…”
Section: Introductionunclassified
“…Estudos histológicos mostram que as fibras de elastina se exibem rompidas, entrelaçadas, desorganizadas, delgadas e em forma de fio emergindo a derme adventícia, além disso é possível observar que as mudanças ocorrem em toda a estrutura conjuntiva dérmica, com diminuição no número e volume dos elementos da pele. As áreas mais acometidas são os seios, abdômen, glúteos e coxas, principalmente em mulheres [3][4][5].…”
Section: Introductionunclassified
“…Not surprisingly, improvements in appearance following minimally invasive facial cosmetic procedures can have significantly positive psychosocial effects . Microneedling, also known as percutaneous collagen induction, has demonstrated efficacy for treating a variety of skin conditions including atrophic acne scars, traumatic and burn scars, striae, and skin rejuvenation on all skin types . Histological studies have shown that microneedling can tighten and improve the appearance of photoaged skin.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary epidermal anomaly is also seen at the skin lesions (1,2). In benign scenarios the prevention with topic applications is still a matter of debate but it might work (3,4). Lasers therapy of different types might be also useful (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In benign scenarios the prevention with topic applications is still a matter of debate but it might work (3,4). Lasers therapy of different types might be also useful (3,4). In cases with pathological glucocorticoids excess the removal of the source improves the skin lesions yet not completely, they become white but usually the scars of any aspects are permanent.…”
Section: Introductionmentioning
confidence: 99%